Um tear de histórias: a saga da boneca Emília contra o destino traçado pelas moiras - Araújo, Maria Liduína de (2023)
Monteiro Lobato's children's work marks the Turn of the Key, in the Evolution of our Brazilian Children's Literature. Therefore, by choosing the character Emília as the object of my research, I emphasize the role of reading this children's work in creating children and adolescents with a greater taste for reading and resourcefulness in their ability, through the wonderful world of Sítio do Picapau Amarelo, criticism and astute way of positioning themselves in the real World of adults who lost their Gifts and Talents in the JOURNEY of their complex Lives in Society. Thus, the performative Emília, during her evolution, used her body, with grimaces and various demonstrations of her Discontent in Being, completely manipulated. However, with the ability to Emission his thinking, through the Gift of Speech acquired, after "accidentally" swallowing Doctor Caramujo's talking pills, all his eloquent orality echoed throughout the Wonderful Universe of Sítio do Picapau Amarelo and, thus, expanded the her Performance from a "simple rag doll" to a talking rag doll. In this way, those retracted thoughts and bodily expressions of hers, with the acquisition of spoken language, increased her Performative Power and freed Emília from the management by others of her Body from a "simple rag doll" to a rag doll with a Life of its own, i.e. , her Destiny of Being Silenced ended and she was reborn like a Phoenix to begin a New Cycle in the weaving of her stories within the Lobatian work. This study discusses the saga of the doll Emília, which began in the work Reinações de Narizinho, against the pre-established (destiny), when she began to speak and show all her versatility as a rag doll that became people, through the acquisition of " Gift of Speech", acquired by swallowing Doctor Caramujo's talking pills. Thus, because she does not want to follow the rules that impede people's creativity, Emília, in Reinações de Narizinho (1931) by Monteiro Lobato, develops the role of the critical character, in order to circumvent the barriers of destiny, becoming changeable through his creativity and cunning against the Fates. Therefore, Emília works as a warrior against order, or rather, through her actions she demonstrates that she does not accept that destiny is governed by the Moiras and seeks to weave her own stories. This battle is continued in two works that describe Greek mythical cycles: The Minotaur (1939) and The Twelve Labors of Hercules (1944). In this context, this work aims to establish a connecting thread between the destiny pre-determined by the Moiras and Emília's mythical attitudes described in Reinações de Narizinho through a discussion about the rhetorical language in the rag doll's journey and her "making to happen". The fabric of this work is based on the philosophical thinking of the utopian city in Plato's work The Republic, in the art of “Beautiful”" evidenced in Poetic Art, by Aristotle, and in the investigation into the Reception of some Myths, some Goddesses and other female characters of Greco-Latin Literature, such as the Liberatropa of the Lysistrata by Aristophanes (Pompeus, 1997), male characters such as Odysseus of the Odyssey, some theorists, such as Frey (1973), and other critics who contributed to the fabric of this study of comparative literary criticism between Brazilian Children's Literature and other Classical Cultures in the construction of the wonderful Universe of Sítio do Picapau Amarelo and the wise talking rag doll, the Brazilian "Marquesa de Rabicó", Emília.